Seberapa penting manajemen risiko dalam suatu perusahaan dan perbankan - Rozikin, Mochammad Ainur (Maliki Interdisciplinary Journal, 2024)
Sharia finance is an economic sector in Indonesia that is experiencing very rapid growth in the global financial industry. Banking financial institutions are one of the financial institutions that have very strategic value in the running of a country's economy. Risk is often defined as uncertainty that is always faced by every company/agency in the service, trade and banking sectors. This research aims to find out how important risk management is to be implemented in companies and banks. The method used in this research is literature study research. The results of this research are that risk management is very important in a company and banking, because risk management has a very crucial role in the success and sustainability of the company. The use of this risk management strategy should not be haphazard, because each company has different risks depending on what field it is in and how risk management is implemented in the company.